Different ideas associated renal malformation and laminin Î±5 expression caused by maternal nicotine exposures - Shariati-Kohbanani, M; Taghavi, M M; Shabanizadeh, A; Jafari Naveh, H R; Taghipour, Z; Kazemi Arababadi, M (Cellular and Molecular Biology, 2016)
The number of smokers is increasing specially in pregnant mothers and millions of children with health problems are born from the smoker mothers. Nicotine as a toxic substance crosses from placenta and accumulates in the developing organs of fetus. In this study, the effects of maternal nicotine exposure on expression levels of kidney laminin Î±5 in newborn mice were examined. Timed pregnant mice were injected subcutaneously with nicotine at a dose of 2 mg/kg/day from day 7 of gestation to the last day of the pregnancy (Group 1) and from day 7 until the two weeks of postnatal (Group 2). Sham control groups were injected with saline. After the last injection, all the newborn mice were anesthetized; their kidneys were removed and prepared for analysis of mRNA and protein expression of laminin Î±5 using Real-Time PCR and immunohistochemical techniques, respectively. Our results showed that mRNA levels of kidney laminin Î±5 in newborn mice were increased in group 1 when compared to sham control group and also group 2. Immunohistochemical analysis demonstrated that the protein levels of laminin Î±5 in the glomerulus have significantly increased in group 1 when compared to group 2. In the proximal convoluted tubules, the parameter had a high significant increase in group 1 in comparison to control and also group 2. According to the results, it seems that maternal nicotine exposure may induce abnormal laminin Î±5 expression which may cause defects in kidney function during life time.